Kritik Epistemologi Islam dalam Islamologi Terapan - Isa Anshori (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2015)
This article discusses the critique of Islamic epistemology within applied Islamology. The writer concludes that Islamic epistemology is an episteme which has been originally derived from Islamic doctrines. It can be obtained through a number of methods. The first method is a revelation, which has absolute truth. The second way is the reason, which becomes a potency blessed by God to all humankind. Through impressions attained by the five senses, the reason uses them as a source of contemplation to draw conclusions. This episteme contains, however, a relative truth. The third method is kashfî. This episteme is also named as ‘irfanî episteme, which had successfully grown within Sufism tradition where the source of knowledge is experienced, namely al-ru’yat al-mubâshirah (direct experience). The last-mentioned episteme is founded on the dichotomy between exoteric and esoteric aspects where the hierarchy of esoteric knowledge is higher than the exoteric ones as the first possesses a divine basis. The critique of Islamic epistemology within applied Islamology is oriented towards the domination of scientific epistemology or modern epistemology, which recognizes positivism or scientific knowledge as the sole method employed by modern people to gain knowledge. The fundamental difference between the scientific-rational episteme and the Islamic episteme rests within each worldview.